Influence of Environmental Temperature on the Corrosion Resistance of Various Aluminum Alloys: an Experimental Study - Kazem Reza Kashyzadeh; Siamak Ghorbani; Andrey S. Averyanov (RUDN Journal of Engineering Research, 2025)
One of the biggest challenges that engineers encounter in a variety of industry sectors is corrosion. The current research focuses on the corrosion behavior of various types of aluminum alloys widely used in the industry. In this regard, aluminum alloys Al2024, Al6061, and Al7075 were tested. Also, the effect of environmental temperature on the corrosion rate of each group of materials was investigated. Three statistical parameters, including total corroded area, corrosion rate (total corroded area to total sample area), and the maximum size of corroded point, were measured as corrosion indicators in the samples. In addition, the surface hardness of the samples was measured and presented by the Brinell method. Finally, the weakest aluminum alloy against corrosion under different temperature conditions was introduced. The corrosion test conducted in the presence of cold air produced the maximum hardness in any of the aluminum alloys (2024, 6061, and 7075) that were examined. Aluminum 7075 has the lowest corrosion resistance, while aluminum 6061 has the strongest corrosion resistance when various testing conditions are taken into account.